Solutions Containing a Statherin-Derived Peptide Reduce Enamel Erosion in vitro - Reis, Fabiana Navas; Francese, Monique Malta; Da Silva, Natara Dias Gomes; Pelá, Vinícius Taioqui; Câmara, João Victor Frazão; Trevizol, Juliana Sanches; Honório, Heitor Marques; Crusca, Edson [UNESP]; Marchetto, Reinaldo [UNESP]; Buzalaf, Marília Afonso Rabelo (Karger Publishers, 2023)
The effect of solutions containing a statherin-derived peptide (Stn15pSpS) on the protection against enamel erosion in vitro was evaluated. Bovine enamel specimens were divided into 4 groups (n = 15/group): (1) deionized water (negative control), (2) Elmex Erosion Protection™ (positive control), (3) 1.88 × 10-5 M Stn15pSpS, and (4) 3.76 × 10-5 M Stn15pSpS. The solutions were applied on the specimens for 1 min. Stimulated saliva was collected from 3 donors and used to form a 2-h acquired pellicle on the specimens. Then, the specimens were submitted to an erosive pH-cycling protocol 4 times/day, for 7 days (0.01 M HCl pH 2.0/45 s, artificial saliva/2 h, and artificial saliva overnight). The solutions were applied again during pH-cycling, 2 times/day for 1 min after the first and last erosive challenges. Enamel loss (μm) was assessed by contact profilometry. Data were analyzed by Kruskal-Wallis and Dunn's test (p < 0.05). The best protection against erosion was conferred by Elmex Erosion Protection that significantly differed from all the other treatments, followed by the solutions containing Stn15pSpS, regardless of the concentration. However, 3.76 × 10-5 M Stn15pSpS did not differ from the negative control. The solution containing the lower concentration of Stn15pSpS protected against erosion in vitro, which should be confirmed using protocols that more closely resemble the clinical condition.
Keywords: Enamel pellicle; Human; Statherin protein; Tooth erosion